Case Report: Anti-NF186+ CIDP After Receiving the Inactivated Vaccine for Coronavirus Disease (COVID-19) - Wen, Shirui; Huang, Kailing; Zhu, Haoyue; Li, Peihong; Zhou, Luo; Feng, Li (Frontiers in Neurology, 2022)
Corona Virus Disease 2019 (COVID-19), the novel coronavirus disease, is now a global pandemic. Vaccination can significantly reduce the mortality rate caused by the severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2). There are currently several effective vaccines that have been introduced. Inactivated COVID-19 vaccine is one of these options and is generally considered safe. Neurofascin (NF) plays an important role in keeping the functionality of the node of Ranvier. We report here a rare case of anti-NF186+ chronic inflammatory demyelinating polyneuropathy (CIDP) in a 23-year-old male patient who was vaccinated with inactivated COVID-19 vaccine prior to the onset. This report adds a new possible rare side effect of a COVID-19 vaccine and provides a case for the clinical effectiveness of rituximab (RTX) in patients with anti-NF186+ CIDP.